Exaggerating character motions using sub-joint hierarchy - Kwon, J. Y.; Lee, I. K. (Computer Graphics Forum, 2008)
Motion capture cannot generate cartoon-style animation directly. We emulate the rubber-like exaggerations common in traditional character animation as a means of converting motion capture data into cartoon-like movement. We achieve this using trajectory-based motion exaggeration while allowing the violation of link-length constraints. We extend this technique to obtain smooth, rubber-like motion by dividing the original links into shorter sub-links and computing the positions of joints using B´ezier curve interpolation and a mass-spring simulation. This method is fast enough to be used in real time.